Evaluation of Hospital Outcomes Among Very Low Birth Weight Babies in a Community-Level Medical College Hospital - Pervez, Md Imtiaz; Rahman, Ridwana; Khan, Masuma; Sonia, Zannatul Ferdous; Ahmed, A S M Nawshad Uddin (The Journal of Ad-din Women's Medical College, 2025)
Introduction: Very low birth weight (VLBW) babies are at increased risk from a wide range of hazards resulting from immaturity of structure and functions of many organs, which may cause death or permanent damage. Objective: The objective of this study was to evaluate immediate outcomes in VLBW babies. Materials and Methods: This hospital-based prospective cohort study was conducted in the Department of Paediatrics, Kumudini Women’s Medical College and Hospital, Mirzapur, Tangail from August 2008 to July 2009. At enrollment VLBW babies (birth weight <1500 grams) were assessed for gestational age and weight. Patients were followed up daily till discharge or death. The outcome in terms of survival till discharge was recorded. Informed verbal consent from the caregiver was taken before enrolment. Results: A total of 60 VLBW neonates were enrolled in the study. Eight (13.3%) neonates had weights below 1000 grams and 52 (86.7%) had 1000-1499 grams. Five (8.3%) neonates had gestational age <28 weeks, 44 (73.3%) were 29-32 weeks, and 11(18.3%) were 33-36 weeks. Maternal age, place, and mode of delivery were significant contributory factors. In the present study, 35(59%) of VLBW babies expired; 100% of babies died below 1000 grams. Neonatal mortality showed an inverse relationship with birth weight and gestational age. Conclusion: Proper antenatal care should be encouraged throughout the country to prevent the neonatal mortality associated with VLBW infants. Management of labor is important and facilities for the management of high-risk pregnancy should be made available widely. Immediate management of newborns after birth can prevent the worst hospital outcomes in our country. The Journal of Ad-din Women's Medical College; Vol. 12 (2), July 2024; p 21-25